2018
DOI: 10.21614/chirurgia.113.3.353
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutical Aspects Regarding Pancreatic Pseudocysts

Abstract: Chirurgia, 113 (3), 2018 www.revistachirurgia.ro 353 RezumatFrecvent apărute că şi complicaţii ale pancreatitei, pseudochistele pancreatice sunt entităţi rare, pentru tratamentul cărora s-au dezvoltat de-a lungul timpului multiple tehnici terapeutice, variind de la metode minim invazive la tehnici complexe de chirurgie clasică. Pseudochistele simptomatice, cele de mari dimensiuni precum şi cele ce suferă complicaţii evolutive de timpul hemoragiei, suprainfectiei şi rupturii au indicaţie de drenaj. Alegerea m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 60 publications
(96 reference statements)
0
2
0
Order By: Relevance
“…Partial pancreatectomy is mostly indicated for extensive chronic pancreatitis in the presence of multiple small pseudocysts in the pancreas, large pseudocysts causing biliary and pancreatic duct obstruction, duodenal infarction, haemorrhage and potentially with severe symptoms [18]. Study showed [30] that the morbidity and mortality rate in patients undergoing open surgery is less than 1%, complication rate is nearly 30% and recurrence rate is 6%. With the popularity of endoscopic cyst drainage, open internal drainage of simple pseudocysts has been gradually replaced by endoscopic drainage, while external drainage has now been largely eliminated by percutaneous transluminal drainage due to the high trauma and complications of indwelling catheters.…”
Section: Discussionmentioning
confidence: 99%
“…Partial pancreatectomy is mostly indicated for extensive chronic pancreatitis in the presence of multiple small pseudocysts in the pancreas, large pseudocysts causing biliary and pancreatic duct obstruction, duodenal infarction, haemorrhage and potentially with severe symptoms [18]. Study showed [30] that the morbidity and mortality rate in patients undergoing open surgery is less than 1%, complication rate is nearly 30% and recurrence rate is 6%. With the popularity of endoscopic cyst drainage, open internal drainage of simple pseudocysts has been gradually replaced by endoscopic drainage, while external drainage has now been largely eliminated by percutaneous transluminal drainage due to the high trauma and complications of indwelling catheters.…”
Section: Discussionmentioning
confidence: 99%
“…The current consensus indicates that only approximately 30% of PCLs are pseudocysts. This change in tendency results primarily from the development of EUS-FNA and its increased use [ 24 , 25 , 26 ]. Pseudocysts contain fluid collection surrounded by a wall of fibrous tissue without epithelium lining and are connected with the pancreatic duct system, either as a direct communication or indirectly through the pancreatic parenchyma.…”
Section: Types Of Incidental Pancreatic Lesionsmentioning
confidence: 99%